E-Scripts and Cell Phones: A Blessing or Curse?. Issue 4 (October 2017) - Harris, Susie T.; Bell, Paul D.; Baker, Elizabeth A.
Abstract : E-scripts have been used as part of computerized provider order entry implementation for several years now, particularly with the passage of the American Recovery and Reinvestment Act, Meaningful Use, the Health Information Portability and Accountability Act, the Health Information Technology for Economic and Clinical Health Act, and other laws and regulations. This case study seeks to focus on 2 specific aspects of the effect of increasing electronic technology within health care: e-prescriptions and cell phones or smartphones.